Effect of Miricorilant, a Selective Glucocorticoid Receptor Modulator, on Olanzapine-Associated Weight Gain in Healthy Subjects: A Proof-of-Concept Study - Hunt, Hazel J; Donaldson, Kirsteen; Strem, Mark; Tudor, Iulia Cristina; Sweet-Smith, Suzanne; Sidhu, Sharan (Journal of clinical psychopharmacology, 2021)
Antipsychotic medications, including olanzapine, are associated with substantial weight gain and metabolic disturbances. We sought to determine whether coadministration of miricorilant, a selective glucocorticoid receptor modulator, with olanzapine can ameliorate these effects. Sixty-six healthy men were enrolled in a 2-week, randomized, double-blind, placebo-controlled trial. The primary objective was to evaluate changes in body weight after 14 days coadministration of olanzapine (10 mg) + miricorilant (600 mg) compared with olanzapine (10 mg) + placebo. Secondary objectives included evaluating (a) the safety and tolerability of the combination; (b) the effects of the combination on glucose, insulin, insulin resistance, and triglycerides; and (c) the impact of the combination on hepatic enzymes. Subjects administered olanzapine + miricorilant gained less weight than subjects administered olanzapine + placebo (mean weight gain on day 15, 3.91 kg vs 4.98 kg; difference between groups, -1.07 kg; 95% confidence interval, -1.94 to -0.19; P = 0.017]). Compared with the placebo group, coadministration of miricorilant with olanzapine was associated with smaller increases in insulin (difference, -3.74 mIU/L; P = 0.007), homeostatic model assessment of insulin resistance (difference, -0.47; P = 0.007), triglycerides (difference, -0.29 mmol/L; P = 0.057), aspartate aminotransferase (difference, -32.24 IU/L; P = 0.009), and alanine aminotransferase (difference, -49.99 IU/L; P = 0.030). Miricorilant may provide a promising option for ameliorating the detrimental effects of olanzapine, and investigation of this medication in patients affected by antipsychotic-induced weight gain is warranted. Two phase 2 studies of miricorilant in patients with recent and long-standing antipsychotic-induced weight gain are currently in progress.